(untitled) (Interdisciplinary Studies Journal, 2024)
This study aims to analyze, in the perception of teachers at a school in a municipality in the northwest region of the state of Rio Grande do Sul, the knowledge, actions developed and challenges for developing the School Health Program (PSE). This is a qualitative, exploratory study of the case study type, in which five teachers from a public municipal school in a municipality in the state of Rio Grande do Sul participated. An interview was used as an instrument. The data were interpreted using the content analysis technique. The results indicated that teachers consider PSE important, but that it needs to be better organized, happen more frequently at school, be more routine and not just with specific actions. In this context, it is concluded that facing the challenges in implementing the PSE involves adjustments in the integration between the sectors involved.